The Effectiveness of Kinesio-Taping and Muscle Energy Technique Among Postpartum Females with Sacro-iliac Joint Dysfunction (Medical Forum Monthly, 2022)
Objective: Our study aimed to compare the effects of Kinesio-Taping and Muscle Energy Technique in managing pain, disability, and pelvic inclination among postpartum females with sacroiliac joint dysfunction.Study Design: A single-blinded randomized controlled trial studyPlace and Duration of Study: This study was conducted at the outpatient department of Physical therapy in a tertiary care hospital in Karachi, Pakistan, from May 2022 to Aug 2022.Materials and Methods: Fifty-two postpartum females with sacroiliac joint dysfunction aged between 20-35 years, randomly divided into groups A and B (n=26 in each group), were examined for the intensity of pain, physical disability, and pelvic asymmetry. The outcomes were assessed pre and post of four weeks of treatment; performed twelve sessions of Kinesio-taping for group A and MET for group B.Results: Kinesio-taping and MET showed a significant difference in pre and post readings with the p-value <0.05 in all outcome measures of pain, disability, and pelvic asymmetry. The post-mean differences between the groups demonstrated no significant difference (p>0.05).Conclusion: MET and K-taping both were practical management approaches for reducing pain and physical disability and decreasing pelvic asymmetry among postpartum females with sacroiliac dysfunction.